PENGARUH STRUKTUR MODAL, KEBIJAKAN UTANG, DAN UMUR PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Zul Fahri; Sumarlin Sumarlin; Raodahtul Jannah (ISAFIR: Islamic Accounting and Finance Review, 2022)
This research aims to test the influence of capital structure, debt policy, and the age of companies on the value of property and real estate sector companies listed on the Indonesia Stock Exchange in 2016-2020. The study also tested whether the size of companies was able to moderate their respective relationships between capital structure, debt policy, and the age of the company to the company's value. The study used a quantitative approach with a comparative causal type. The population in this study is all property and real estate sector companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling techniques using purposive sampling. The data used in this study is secondary data accessed through the IDX website. Data analysis uses multiple regression analysis to hypothesize capital structure, debt policy, and corporate age, as well as an analysis of the value of absolute difference for capital structure, debt policy, and the age of the company to the company's value with the size of the company as a moderation variable. The results of this study showed that the structure of capital and age of the company had a positive and significant effect on the value of the company, while the debt policy had a negative and significant effect on the value of the company. The moderation variable is the size of the company being able to moderate the relationship between the capital structure and debt policy to the value of the company, but not able to moderate the relationship between the age of the company to the value of the company.